Sexist language : terms of reference for women and men / Ramesh Nair - Nair, Ramesh (Academy of Language Studies & UPENA, 2005)
This study analyses the usage of various terms of reference for women and men in two local English language magazines. The magazines were selected to represent local magazines that have a gender specific audience in mind. This study is specifically aimed at identifying terms of reference that are sexist. A questionnaire was posed to investigate how respondents viewed terms of reference which western feminists and linguists consider sexist. The analysis reveals that more sexist terms are used to refer to women than to men. Interestingly, the analysis also shows that the respondents did not concur with western feminists on what should be regarded as sexist language.